Features of use of agricultural drones in crop production technologies (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The article presents a generalization of the production cycle regarding the features of the machine use of agricultural drones in crop production technologies. Applied methods and initial data of agricultural drone technologies in agriculture have been developed taking into account the diversity of technological operations. In the course of the research, fourteen tasks are presented that modern agricultural drone technologies solve. The author outlines a six-level full cycle of agricultural drone monitoring of crops. At the same time, accounting for the initial data allows for the process of forming a visualization of field surveys from agricultural drones. The author recreates the features of video and photography from a height, the functionality of thermal imaging cameras of agricultural drones for agriculture, which allows monitoring to be brought as close as possible to the real cycle of crop production.
Keywords: agricultural drone; technology; machine use; method